Facility reference level for common x-ray procedures: A preliminary study - Satharasinghe, DM; Jeyasugiththan, J; Pallewatte, AS; Wanninayake, WMNMB (Asia-Oceania Congress of Medical Physics (AOCMP), 2020)
Ionizing radiation is an essential tool in medical diagnosis and it brings great benefit to the patient. However, the associated risks due to the radiation are unavoidable. Therefore, close monitoring of radiation exposure should be performed in order to control the potential harm. As an advisory measure to improve optimization of patient’s radiation protection, Diagnostic Reference Levels (DRLs) was introduced by the International Commission on Radiation Protection (ICRP). The present study aims at the evaluation of the doses and their variation for selected x-ray procedures used by a single institution in Sri Lanka to determine a possible institutional DRL. The study included dose data and exposure parameters from 218 chest-Postero Anterior (PA), 33 abdomen-Antero Posterior (AP), 85 lumbar spine AP and 88 lumbar spine-Lateral (LAT) projections of patients (age between 19-78 years). The 3rd quartile dose values for the above projections were 16, 256, 155, 455 µGy.m2 respectively. Further, the above dose values were compared with international DRLs and we found that the lumbar spine lateral projection and abdomen AP are with higher dose levels. This preliminary study provides information on the selected study setting only however, can be used as a reference for quality improvement programs by others.
Keywords: institutional diagnostic reference level; IDRL; Diagnostic reference level; DRL; ionizing radiation; x-ray